Teacher Gender Effects on Students' Socio-Emotional Skills - Greta Morando; Sonkurt Sen (Institute of Labor Economics (IZA), 2025)
Socio-emotional skills are recognized as key factors influencing both early and later life outcomes. However, there is limited evidence on how these skills are shaped within the classroom environment. This paper uses nationally representative survey data from England to examine the impact of teacher gender on students' socio-emotional skills. We employ a student fixed effects model. Our findings show that male teachers positively influence male students' prosocial behavior, while negatively affecting female students' peer problems. We provide support for the role model hypothesis and present novel evidence on how parents respond to teacher-student gender match by adjusting their investment strategies for daughters.
Keywords: D91; I21; J13; J24; 330; socio-emotional skills; teachers; gender; child development